John Owen as proto-social trinitarian? Reinterpreting Owen and resisting a recent trend - Kieser, Ty (Scottish journal of theology, 2021)
Contrary to much of the recent literature on the trinitarian theology of John Owen, which often ascribes radical personal distinction to his account of triune relations and actions, this paper argues that Owen's account of distinct divine persons and trinitarian actions ought not to be contrasted with his theological forebears: Augustine, Thomas Aquinas and Calvin. Instead, his account of trinitarian ontology and operation is thoroughly consistent with (and dependent upon) the Augustinian principles that these interpreters suspect Owen is rejecting. The argument unfolds by presenting four putative points of strong personal distinction in John Owen's trinitarian theology and then reinterpreting each of the themes and passages that these four points are supposedly rooted in, evidencing his Augustinian account of trinitarian unity and distinction.